MEDIA PEMBELAJARAN MATEMATIKA BERBASIS ANDROID PADA MATERI PROGRAM LINEAR - Putri Nandita Apsari; Swaditya Rizki (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The objective of this research and development was to produce a product of learning media based on android that were valid and practical to use for the student. This research type was Research and Development (R&D). The model used in this research was ADDIE model consisting of 5 stages. The instruments of data collection used the questionnaires product validation by experts and practicality by students. Based on the validations process were obtained the result that the developed learning media fulfill very feasible category, with the average percentage of 84.5%, which means that developed learning media was very valid. While the results of small group trials were obtained the result that the response of the students who numbered 10 students with an average of 88.1% stated strongly agree which means learning media developed was very practical. Based on predetermined criteria, the android-based mathematics learning media on linear program material developed fulfill the valid and practical criteria.